Mu Opioid Receptor Gene: New Point Mutations in Opioid Addicts - Amin Dinarvand; Ali Goodarzi; Nasim Vousooghi; Mehrdad Hashemi; Rasoul Dinarvand; Fahimeh Ostadzadeh; Ahad Khoshzaban; Mohammad-Reza Zarrindast (Basic and Clinical Neuroscience, 2014)
Introduction: Association between single-nucleotide polymorphisms (SNPs) in mu opioid receptor gene and drug addiction has been shown in various studies. Here, we have evaluated the existence of polymorphisms in exon 3 of this gene in Iranian population and investigated the possible association between these mutations and opioid addiction.